Efficient CO2 Reduction to HCOOH with High Selectivity and Energy Efficiency over Bi/rGO Catalyst. Issue 5 (25th February 2020) - Duan, Yan‐Xin; Liu, Kai‐Hua; Zhang, Qi; Yan, Jun‐Min; Jiang, Qing
Abstract: The electroreduction of carbon dioxide (CO2 ) to value‐added fuels is of great significance to meet the ever‐increasing energy and environmental challenges. So far, desirable selectivity and Faradaic efficiency for CO2 reduction can be obtained over most electrocatalysts. However, improving cathodic energy efficiency is still neglected in research. Herein, a facile reduction method is first presented to synthesize the ultrafine non‐noble bismuth (Bi) nanoparticles anchored on rGO (Bi/rGO). As expected, the Bi/rGO catalyst exhibits excellent electrochemical performance on CO2 reduction to form formic acid (HCOOH), with very high Faradaic efficiency (up to 98%), favorable stability (over 12 h), and especially outstanding cathodic energy efficiency (up to 71%). Further, density functional theory (DFT) calculations are performed to investigate the possible reaction mechanism for reduction of CO2 to HCOOH. Abstract : The cathodic energy efficiency (EE) is a significant parameter to evaluate the performance of CO2 electroreduction; however, it is always neglected in the research. Here, ultrafine bismuth nanoparticles anchored on reduced graphene oxide (rGO) (Bi/rGO) show excellent activities for CO2 reduction to HCOOH with high Faradaic efficiency (FE, 98%), low overpotential, favorable stability, and especially outstanding EE (71%).